2020
DOI: 10.1519/jsc.0000000000003596
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Load–Velocity Relationship to Predict 1 Repetition Maximum During Deadlifts Performed With and Without Lifting Straps: The Accuracy of Six Prediction Models

Abstract: Jukic, I, García-Ramos, A, Malecek, J, Omcirk, D, and Tufano, JJ. Validity of load–velocity relationship to predict 1 repetition maximum during deadlifts performed with and without lifting straps: The accuracy of six prediction models. J Strength Cond Res 36(4): 902–910, 2022—This study aimed to compare the accuracy of six 1 repetition maximum (1RM) prediction models during deadlifts performed with (DLw) and without (DLn) lifting straps. In a counterbalanced order, 18 resistance-trained men performed 2 session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 32 publications
7
55
1
Order By: Relevance
“…However, studies have also shown that the PUSH devices for measuring and monitoring velocity may provide inaccuracies ( Jovanovic & Jukic, 2020 ; Pérez-Castilla et al, 2019 ). Therefore, it is speculated, that the combination of innaccuracy (overestimating 1-RM) when predicting the 1-RM from the load-velocity relationship with different regression equations ( Banyard, Nosaka & Haff, 2017 ; Hughes et al, 2019 ; Jukic et al, 2020 ; Lake et al, 2017 ; Ruf, Chéry & Taylor, 2018 ), together with potentially innaccuracies in velocity measurement devices ( Jovanovic & Jukic, 2020 ; Pérez-Castilla et al, 2019 ), could be a possible limitation for accurate predicting intensity of the real 1-RM when using velocity targets to prescribe load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have also shown that the PUSH devices for measuring and monitoring velocity may provide inaccuracies ( Jovanovic & Jukic, 2020 ; Pérez-Castilla et al, 2019 ). Therefore, it is speculated, that the combination of innaccuracy (overestimating 1-RM) when predicting the 1-RM from the load-velocity relationship with different regression equations ( Banyard, Nosaka & Haff, 2017 ; Hughes et al, 2019 ; Jukic et al, 2020 ; Lake et al, 2017 ; Ruf, Chéry & Taylor, 2018 ), together with potentially innaccuracies in velocity measurement devices ( Jovanovic & Jukic, 2020 ; Pérez-Castilla et al, 2019 ), could be a possible limitation for accurate predicting intensity of the real 1-RM when using velocity targets to prescribe load.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid such inaccuracies, Weakley et al (2020) recommended in their review to periodically assess the load-velocity relationship for accurate prescription of relative loads. However, several studies have presented less favourable findings with respect to quantifying 1-RM using the load-velocity relationship ( Banyard, Nosaka & Haff, 2017 ; Hughes et al, 2019 ; Jukic et al, 2020 ; Lake et al, 2017 ; Ruf, Chéry & Taylor, 2018 ). In these studies, the use of different regression equations to predict 1-RM from the load-velocity relationship mostly tended to overestimate the predicted 1-RM, when compared to the real 1-RM lifted.…”
Section: Introductionmentioning
confidence: 99%
“…García-Ramos et al [ 38 ] have presented data that suggest that MV is the most appropriate variable to monitor during ballistic exercises, such as the bench press throw, performed in a Smith machine. Conversely, Jukic et al [ 39 ] have recently reported that when the MV is used as part of a five-point linear equation, the deadlift 1-RM is overestimated by 7.3 ± 6.6 kg when compared to the actual 1-RM. In the present study when a four-point linear regression analysis was used, the predicted 1-RM (69.4 ± 12.9 kg) was significantly less (−6.59 ± 11.13 kg, p = 0.023, d = −0.52) than the criterion measure (76.5 ± 12.4 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Besides statistical modeling, LvR-profiling is a widely accepted approach to predict 1RM performance that has, in fact, not yet been used for weightlifting competition exercises (i.e., snatch, clean and jerk). However, being similar to the snatch and clean, recent research was conducted on the prediction accuracy of 1RM in the power clean and deadlift exercise using individual LvR profiles [ 11 , 12 , 25 ]. For instance, Haff, Garcia-Ramos, and James [ 11 ] used the individual LvR to predict the 1RM power clean performance in recreationally trained males aged 26 years.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported a measurement error (systematic bias ± SDD) of 1.4 ± 7.2 kg. Additionally, the individual LvR was used for the deadlift exercise to predict 1RM performance in resistance trained men aged 24 years [ 12 , 25 ]. Results indicated measurement errors (systematic bias ± SDD) of 0.6 ± 8.5 kg [ 25 ] and 0.7 ± 4.7 kg [ 12 ].…”
Section: Discussionmentioning
confidence: 99%